Schulman, Lyndon B. Johnson And American Liberalism - A Brief History With Documents - Coate, Charles (Teaching History: A Journal of Methods, 1997)
Bruce Schulman has written a fine little book on Lyndon Johnson, one that instructors and students will enjoy reading. The beginning 162-page interpretive essay demonstrates mastery of the growing Johnson literature and offers concise and readable presentation, lively use of colorful anecdote, and judicious interpretation. Specialists will be impressed with his ability to comment on most of the many controversies about Johnson’s life and politics.